The Padovan Sequence and the plastic number: a prior analysis and a priori (Research, Society and Development, 2019)
The present work presents the two initial phases of Didactic Engineering with the theme involving the study of the Sequence of Padovan and the plastic number which was the object of study primarily by Richard Padovan (1935-?) And Gérard Cordonnier (1907 - 1977). In order to transform the Padovan numbers into a content to be taught, a theoretical investigation will be carried out, presenting teaching guides and didactic transposition around this linear and recurrent sequence, so that there is greater exploitation in the academic teaching to the study of said sequence. Finally, academic improvements will be made through a historical, mathematical and epistemological context.